Sales Negotiations in Professional Service Firms An Exploratory Study on Agenda Setting and Issue Management - Prat, Mireia. (BestMasters,, 2014)
This research study brings theoretical insights on real-life negotiations in sales of professional services in Spain and Germany. From the interview data obtained through an exploratory study based on a grounded theory approach, several factors that affect and determine agenda setting and issue management have emerged. It has been spotted that industry standards rather than negotiation strategy determine agenda setting and that issues about content are usually agreed on before negotiating price and bureaucratic conditions, being the degree of "productization" of Professional Service Firms a variable that needs to be taken into account. Moreover, a pattern has been found in sales negotiations of consulting companies dealing with client companies with an organized purchasing department, which has been labeled as "multi-party sequential negotiation model".   Contents Agenda setting Issue management Multi-party sequential negotiation Productization of Professional Services   Target Groups Researchers and students in the field of business management and negotiation Professional Service Firms' decision makers, Sales Managers, Purchasing Managers and professionals dealing with negotiations   The Author Mireia Prat studied Business Management at Universitat Pompeu Fabra of Barcelona, and obtained her Master of Science degree in Management and Marketing at Freie Universität of Berlin.